A Forward Genetic Screen Targeting the Endothelium Reveals a Regulatory Role for the Lipid Kinase Pi4ka in Myelo- and Erythropoiesis - Safiyyah Ziyad; Jesse D. Riordan; Ann M. Cavanaugh; Trent Su; Gloria E. Hernandez; Georg Hilfenhaus; Marco Morselli; Kristine Huynh; Kevin Wang; Jau-Nian Chen; Adam J. Dupuy; M. Luisa Iruela-Arispe (Cell Reports, 2018)
Summary: Given its role as the source of definitive hematopoietic cells, we sought to determine whether mutations initiated in the hemogenic endothelium would yield hematopoietic abnormalities or malignancies. Here, we find that endothelium-specific transposon mutagenesis in mice promotes hematopoietic pathologies that are both myeloid and lymphoid in nature. Frequently mutated genes included previously recognized cancer drivers and additional candidates, such as Pi4ka, a lipid kinase whose mutation was found to promote myeloid and erythroid dysfunction. Subsequent validation experiments showed that targeted inactivation of the Pi4ka catalytic domain or reduction in mRNA expression inhibited myeloid and erythroid cell differentiation in vitro and promoted anemia in vivo through a mechanism involving deregulation of AKT, MAPK, SRC, and JAK-STAT signaling. Finally, we provide evidence linking PI4KAP2, previously considered a pseudogene, to human myeloid and erythroid leukemia. : Using transposon mutagenesis that targets the endothelium, Ziyad et al. identify Pi4ka as an important regulator of hematopoiesis. Loss of Pi4ka inhibits myeloid and erythroid cell differentiation. Previously considered a pseudogene in humans, PI4KAP2 is shown to be protein-coding and a negative regulator of PI4KA signaling. Keywords: erythropoiesis, myelopoiesis, hematopoiesis, leukemia, hemogenic endothelium, lipid kinase, Pi4ka, PI4KAP2, Akt, Erk